Interpretation of Sayyang Pattuqduq Cultural Symbols of Mandar People in Majene Regency West Sulawesi - Lutfiah; Sonni, Alem Febri; Saeni, Rahman (Mediakita, 2024)
This study aims to interpret the symbols, meanings, and values of the Sayyang Pattuqduq tradition in the Mandarese community in Majene Regency, West Sulawesi. The study is descriptive qualitative and uses a communication ethnography approach and semiotic analysis method. The primary and secondary research data collection methods include field observations, interviews, and documentation. Literature study and communication ethnography methods are also applied to enrich the variety of research data. In identifying the symbols obtained from a series of interpretations of Sayyang Pattuqduq, Charles Sanders Peirce's semiotic analysis is used, which states that there is a triadic relationship in semiotics that is interconnected between symbols in the celebration, the object of the celebration, and the people who interpret the celebration. The results of this study show that the interpretation of Sayyang Pattuqduq in the community in Majene Regency, West Sulawesi, indicates that there are symbols in the Sayyang Pattuqduq celebration, such as cultural communication symbols, spiritual symbols, symbols of togetherness, and symbols of social stratification. In addition, there are values that each have meaning, among others, as a medium in motivating children, as a function of social solidarity, a function of social integration, as a medium for instilling spiritual values, and as a symbol of stratification by certain groups or communities.